Implementation of Employee Assistance Program (EAP) in Handling Increased Organizational Commitment in Company X - Safitri, Fayzah Rachmawati; Amelasasih , Prianggi (Universitas Muhammadiyah Sidoarjo, 2024)
Organizational commitment is a behavior that is often interpreted as a strong desire of workers to be part of a certain organization, a desire to work hard to achieve organizational goals, and having confidence and awareness to accept organizational values and goals. To increase organizational commitment, researchers use the Employee Assistance Program (EAP) as an intervention, EAP as a workplace-based program designed to assist in the identification and resolution of productivity problems. Human Resources staff must have a high commitment in an organization for maximum development in the company. The method used in this study is a quantitative experiment with subjects from the Human Resources department. The results of this study were 2 people who experienced low organizational commitment, by conducting several consultations with a counceling centered therapy approach which was carried out for 1 month resulting in less effective changes for employees who had organizational commitment problems